2021
DOI: 10.21203/rs.3.rs-517907/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Clinical Prediction Tool for Extended-Spectrum β-Lactamase-Producing Enterobacteriaceae Urinary Tract Infection

Abstract: Background To explore the risk factors of extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-PE) infection through urine samples of hospitalized patients and establish a predictive model to improve treatment outcomes.MethodsThis retrospective study included all patients with an Enterobacteriaceae-positive urine sample at the first affiliated hospital of Jinan university from January 2018 to December 2019. Antimicrobial susceptibility patterns of ESBL-PE were analyzed, and multivariate analysis of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Consistently, Pandit et al (2020) reported that E. coli is essential, and the majorities (64.9 %) of them are MDR, and among them (40.3 %) are ESBL-producing bacteria. Furthermore, it was reported that among cases with UTI, 30 % are ESBL ( Liu et al, 2022 ). CLS I (2012) noted that ESBL was examined in three categories, ESBL screening method, phenotypic confirmation using a double-disc synergy test, and genotypic detection.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Pandit et al (2020) reported that E. coli is essential, and the majorities (64.9 %) of them are MDR, and among them (40.3 %) are ESBL-producing bacteria. Furthermore, it was reported that among cases with UTI, 30 % are ESBL ( Liu et al, 2022 ). CLS I (2012) noted that ESBL was examined in three categories, ESBL screening method, phenotypic confirmation using a double-disc synergy test, and genotypic detection.…”
Section: Discussionmentioning
confidence: 99%